2011
DOI: 10.1093/jjco/hyr165
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Accuracy of Breast Cytological Diagnosis at Seven Institutions in Southern Fukuoka Prefecture, Japan

Abstract: Objective: Cytological examination is inexpensive and relatively simple to carry out and deserves utilization in breast cancer screening. We investigated the status of cytological diagnosis at seven facilities in southern Fukuoka Prefecture, Japan. Methods: We collected data on the criteria for cytological judgments and status of breast cytological diagnosis at seven different facilities in this region. Results: Among 5693 individuals who underwent breast cytological examination, analyses were conducted on 125… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…A recent Japanese study [17] of 5693 FNAC and 7 different laboratories illustrated a great variability between the institutions suggesting likely difference between education of cytologists and the lack of clinical or radiological information (triple diagnosis).…”
Section: Is the Diagnosis Of Fnac Accurate?mentioning
confidence: 99%
“…A recent Japanese study [17] of 5693 FNAC and 7 different laboratories illustrated a great variability between the institutions suggesting likely difference between education of cytologists and the lack of clinical or radiological information (triple diagnosis).…”
Section: Is the Diagnosis Of Fnac Accurate?mentioning
confidence: 99%
“…Therefore, improving the accuracy of FNAB is an important issue, even though we showed that the accuracy of FNAB is as high as that recommended under the relevant clinical guidelines [5]. We believe that there is room for improvement.…”
Section: Discussionmentioning
confidence: 86%
“…Therefore, the present findings should encourage the use of needle biopsy rather than aspiration when this histological type is suspected based on imaging. Furthermore, triple assessment (i.e., clinical, pathological and radiological assessment) should be considered in some cases [5,19]. It is also important that staff receive appropriate pathological and clinical training, and that there is good communication between clinicians and pathological staff [5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations